Financial Performance Indicators Drive Firm Value in State-Owned Companies - Tahawa, Taufik Hidayat B; Wijaya, Henryanto (Indonesian Journal of Innovation Studies, 2025)
General Background: Sovereign Wealth Funds (SWFs) play a crucial role in national economic stability and asset optimization. Specific Background: In Indonesia, Danantara's Investment Management Agency (BPI) operates as the state's SWF, yet empirical studies on financial performance metrics influencing firm value within this context remain scarce. Knowledge Gap: Limited research addresses how profitability, efficiency, and liquidity metrics affect firm valuation in state-managed investment institutions. Aims: This study investigates the impact of Return on Investment (ROI), Net Profit Margin (NPM), and Current Ratio (CR) on firm value in BPI from 2015 to 2024. Results: Using panel data regression via EViews, findings reveal that ROI and CR significantly enhance firm value (t=2.12, p=0.0372; t=4.49, p=0.000), while NPM shows no significant effect (t=0.71, p=0.4773). The model explains 20.38% of firm value variability (R²=0.2038). Novelty: The study highlights that investment efficiency and liquidity—rather than profitability alone—are more critical in state-owned contexts. Implications: These results inform strategic financial management and policy in SWFs, emphasizing the prioritization of ROI and liquidity in enhancing firm valuation. Highlights: Highlights the dominant role of ROI and liquidity in firm valuation. Reveals NPM's limited influence on market-based assessments. Informs SWF strategy through empirical financial analysis. Keywords: Investment Management Agency, Sovereign Wealth Fund, Return on Investment, Net Profit Margin, Current Ratio